EXPERIMENTATION AND POLICY MOBILITIES: - Silva, Diogo Gaspar (2025)
Research on policy mobilities has focused much of its attention on studying how policies-from-elsewhere are learned, mediated and translated into different contexts, either focusing on early (a priori) and late (a posteriori) stages of policymaking processes without encompassing their full scope. In conceptualising policymaking as inherently indeterminate, open-ended and processual, this article introduces the ways in which pilot policy experiments mediate the intersections between a priori and a posteriori phases of policymaking processes. Drawing on the case of three Business Improvement Districts (BIDs) policy programmes in Greater Barcelona (Spain) and Greater Lisbon (Portugal), we discuss the importance of pilot policy experimentation through four key practices: Concept testing, generative learning and knowledge exchange, stakeholder engagement and policy translation. While not always comprehensive, teleological or hermetically separate, these practices serve as a heuristic framework to illustrate how policy experimentation shapes the learning, mediation and translation of urban policies across different policymaking stages. In so doing, we invite policy mobilities scholars to explore further the experimentation with urban policies as arenas in which policies-from-elsewhere are locally constituted and reconstituted across the diverse stages and temporalities of policymaking.